Strategi Pembelajaran Inkuiri dalam Peningkatan Kompetensi Analisis Unsur Cerita - Ardianto, Muhammad Agus (Universitas Wijaya Kusuma Surabaya, 2019)
Learning strategy is action plan (the series of activities including usage method of) and utilization of resources or force in learning. By the use of it and strategy in the education, the purpose of learning will possible. Needed education strategy right to be able to increase the interpretation students in learning analyze intrinsic element of stories. One between education and innovative strategy variatif is inquiry learning strategy. Learning inkuiri spi (strategy) is the learning activities who insists on the thought processes and analytical critically to seek and find your own the questionable a problem. Methods used in research the act of class ( ptk ) this is a qualitative methodology that was produce descriptive analysis with the data collected in student of class xii study results ak 2 for two cycles. The result of this research is ( 1 ) in the first of 38, students there are students or 13 34 % at study analyzing the intrinsic and 25 students 66 % not reaching study analyzing the intrinsic. In the second (2), students or 50 19 increased to percent at study analyzing the intrinsic and 19 students 50 % not reaching ketuntasan study analyzing the intrinsic.